Adaptação da técnica de flutuação de discos foliares em cana-de-açúcar - Oliveira, Viviane Cristina de (2015)
The sugarcane (Saccharum officinarum L) produced nowadays is the result of several genetic improvements made by means of breeding programs. Among the objectives of these programs, one of the most important is obtaining varieties capable of adapting to regions with long periods of drought. The evaluation phase is of extreme importance, given that it allows us to obtain consistent data by using well established evaluation criteria, thus, increasing the reliability of the results and, consequently, assisting in screening and other stages of the program. However, the evaluation methods available for identifying plants tolerant or susceptible to drought present some disadvantages, such as high cost, unfeasible implementation and crop specificities (eg height). These are limiting points for the evaluations in some of the regions. These facts are frequently not included in the project, making the use of these methodologies impracticable. Therefore, one easy and low cost technique that can be applied is the leaf roll floating methodology, used for evaluating the photosynthetic capability of the plant. The objective of the present work was to study the applicability and adaptation of the floating leaf discs technique for the commercial sugarcane variety CTC 15, during the initials phases of the breeding program. First, we tested the applicability of the technique, later, experimenting to achieve a protocol adaptation focusing on C4 photosynthetic systems, the metabolic pathway for sugarcane. The technique was also tested on spinach plants (Spinacea oleracea), a C3 photosynthetic system plant, validation and as experiment control. The experimental design used for all three experiments was completely randomized. For the protocol adaptation experiment, with positive result, we used a 3 x 2 full factorial design (temperature range of 10 - 20°C, 20 - 35°C e 35 - 45°C, and light intensity of 2000 μmol m-2 s-1 e 74 μmol m-2 s-1). The collected data were evaluated by survival rates, using the Kaplan-Meier procedure for analyzing the response of each tested factor. Subsequently, we performed a multifactorial analysis using the Cox Proportional Hazards Regression Analyses (coxph function). After protocol adaptation, the tested technique showed to be applicable for this sugarcane genotype in the temperature ranges of 20-35ºC and 35-45ºC, and light intensity of 2000 μmol m-2 s-1, which are specific conditions for C4 plants.